2020
DOI: 10.1176/appi.ajp.2020.20040417
|View full text |Cite
|
Sign up to set email alerts
|

New Challenges in Addiction Medicine: COVID-19 Infection in Patients With Alcohol and Substance Use Disorders—The Perfect Storm

Abstract: Unfortunately for mariners, the total amount of wave energy in a storm doesn't rise linearly with wind speed, but to its fourth power. The seas generated by a forty-knot wind aren't twice as violent as those from a twenty-knot wind, they're seventeen times as violent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 14 publications
2
53
0
3
Order By: Relevance
“…Much of the evidence makes recommendations around telehealth [14,25,32,33] as well as describing other technology that HR services could utilize, including smartphone and web-based interventions, text messaging for continuing contact and care, machine learning and wearable devices, including digital phenotyping and ecological momentary assessment, biofeedback and virtual reality [34,35]. Lead time and availability of technology (for both services and clients) will limit implementation of these options in the short term with text-messaging, smartphone and web-based interventions being the most simple and quick to roll-out.…”
Section: Ostmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the evidence makes recommendations around telehealth [14,25,32,33] as well as describing other technology that HR services could utilize, including smartphone and web-based interventions, text messaging for continuing contact and care, machine learning and wearable devices, including digital phenotyping and ecological momentary assessment, biofeedback and virtual reality [34,35]. Lead time and availability of technology (for both services and clients) will limit implementation of these options in the short term with text-messaging, smartphone and web-based interventions being the most simple and quick to roll-out.…”
Section: Ostmentioning
confidence: 99%
“…There is conflict between social distancing and the physically, socially and emotionally intimate nature of injecting drug use [39]; for instance, naloxone, as a HR intervention, relies on social connections. Several authors have suggested, that during a pandemic-type situation, naloxone should be made more accessible (with appropriate patient and family education) because of the increased overdose risk resulting from using drugs alone when socially distancing and due to uncertain supply [29,35].…”
Section: Naloxonementioning
confidence: 99%
“…El estar expuesto a situaciones traumáticas y estresantes como la cuarentena prolongada, puede activar el deseo de consumo de las sustancias (ONUDD, 2017), por lo tanto, el impacto psicológico y el estrés debido a la pandemia pueden considerarse un contribuyente significativo al aumento en el riesgo por consumo de sustancias en la población general (McKay & Asmundson, 2020;Spagnolo, Montemitro & Leggio, 2020). artículos La pandemia del COVID-19, su impacto en la Salud Mental y el Consumo El estrés crónico asociado al aislamiento social prolongado, puede desencadenar el consumo sustancias al inducir profundas adaptaciones en los circuitos implicados en redes que involucran motivación, recompensa, comportamiento y control cognitivo.…”
Section: Consumo De Sustancias Psicoactivasunclassified
“…artículos La pandemia del COVID-19, su impacto en la Salud Mental y el Consumo El estrés crónico asociado al aislamiento social prolongado, puede desencadenar el consumo sustancias al inducir profundas adaptaciones en los circuitos implicados en redes que involucran motivación, recompensa, comportamiento y control cognitivo. Estas alteraciones pueden provocar impulsividad, estados emocionales negativos y disminución de la capacidad para regular el estrés de forma adecuada, lo que contribuye a un mayor riesgo de trastornos por consumo sustancias (Spagnolo, Montemitro & Leggio, 2020).…”
Section: Consumo De Sustancias Psicoactivasunclassified
“…And we can identify and refer not only patients but also our beleaguered colleagues who feel alone at sea-to the many lifelines our agencies have cast into what other commentators have referred to as a Perfect Storm of COVID-19 and the opioid crisis (Table). 12…”
mentioning
confidence: 99%